2017
DOI: 10.1002/cam4.1104
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term survival benefit of upfront chemotherapy in patients with newly diagnosed borderline resectable pancreatic cancer

Abstract: The use of neoadjuvant chemotherapy or radiation for borderline resectable pancreatic adenocarcinoma (BL‐PDAC) is increasing. However, the impact of neoadjuvant chemotherapy and radiation therapy on the outcome of BL‐PDAC remains to be elucidated. We performed a retrospective analysis of 93 consecutive patients who were diagnosed with BL‐PDAC and primarily followed at Johns Hopkins Hospital between February 2007 and December 2012. Among 93 patients, 62% received upfront neoadjuvant chemotherapy followed by che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Of those who underwent surgery, an R0 was achieved in 85% and R1 in the remaining 15%. This is similar to the findings of other studies that have evaluated the sensitivity of imaging to determine resectability in these patients 17,18 .…”
Section: Discussionsupporting
confidence: 89%
“…Of those who underwent surgery, an R0 was achieved in 85% and R1 in the remaining 15%. This is similar to the findings of other studies that have evaluated the sensitivity of imaging to determine resectability in these patients 17,18 .…”
Section: Discussionsupporting
confidence: 89%
“…This is similar to the findings of other studies that have evaluated the sensitivity of imaging to determine resectability in these patients. 2729 …”
Section: Discussionmentioning
confidence: 99%
“…The theoretical advantages of an neoadjuvant approach in PDAC includes potential downstage of disease, increase of negative resection margins rates, early treatment for micrometastatic disease and identification of patients with an aggressive tumor biology in whom resection offers no survival benefits. Thus, recent studies have shown the benefit of neo-adjuvant chemotherapy with FOLFIRINOX or gemcitabine and nab-paclitaxel for borderline resectable PDAC (64)(65)(66)(67).…”
Section: Neoadjuvant Therapies In Pdacmentioning
confidence: 99%